ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN PERUSAHAAN LISTRIK NEGARA (PLN) ATAMBUA MENGGUNAKAN METODE STRUCTURAL EQUATION MODELING - Stefanny Anjela Devina Bere; Astri Atti; Meksianis Ndii (JURNAL DIFERENSIAL, 2023)
The State Electricity Company (PLN) is a service company engaged in the electricity sector. Community satisfaction is the level of community feelings after comparing what is received with what is expected. This study aims to determine the effect of service quality, information quality, and interaction quality on community satisfaction in Fatuketi Village, Kakuluk Mesak District, Belu Regency. The number of samples in this study was 100 families using Persero’s PLN services. The data collection technique uses a likert scale questionnaire, which consists of three exogenous variables and one endogenous variable for a total of 11 indicators. The hypothesis in this study is that there is an influence of service quality, information quality, and interaction quality on the level of community satisfaction. The method used is the structural equation modeling (SEM) method. The results obtained show that there is a significant influence of service quality factors (CR = 2.361 ≥ 1.96), information quality (CR = 2.827 ≥ 1.96), and interaction quality (CR = 2.840 ≥ 1.96), on the level of community satisfaction.